Efficacy of synbiotic, probiotic, and prebiotic treatments for irritable bowel syndrome in children: A randomized controlled trial - Baştürk, Ahmet; Artan, Reha; Yılmaz, Aygen (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Irritable bowel syndrome (IBS) is an important health problem that presents serious social burdens and high costs. Our study investigated the efficacy of synbiotic (Bifidobacterium lactis B94 with inulin), probiotic (B. lactis B94), and prebiotic (inulin) treatment for IBS in a pediatric age group. Materials and Methods: This study was randomized, double-blind, controlled, and prospective in design and included 71 children between the ages of 4 and 16 years who were diagnosed with IBS according to the Rome III criteria. The first group received synbiotic treatment [5×109 colony forming units (CFU) of B. lactis B94 and 900 mg inulin]; the second group received probiotic treatment (5×109 CFU B. lactis B94), and the third group received prebiotic treatment (900 mg inulin) twice daily for 4 weeks. Results: Probiotic treatment improved belching–abdominal fullness (p<0.001), bloating after meals (p=0.016), and constipation (p=0.031), and synbiotic treatment improved belching–abdominal fullness (p=<0.001), bloating after meals (p=0.004), constipation (p=0.021), and mucus in the feces (p=0.021). The synbiotic group had a significantly higher percentage of patients with full recovery than the prebiotic group (39.1% vs. 12.5%, p=0.036). Conclusion: Administration of synbiotics and probiotics resulted in significant improvements in initial complaints when compared to prebiotics. Additionally, there was a significantly higher number of patients with full recovery from IBS symptoms in the synbiotic group than in the prebiotic group. Therefore, the twice daily administration of synbiotics is suggested for the treatment of children with IBS.